Cell Cluster Sorting in Automated Differentiation of Patient-specific Induced Pluripotent Stem Cells Towards Blood Cells - Ma, Zhiyao; Toledo, Marcelo Augusto Szymanskide; Wanek, Paul; Elsafi Mabrouk, Mohamed H.; Smet, Francis; Pulak, Rock; Pieske, Simon; Piotrowski, Tobias; Herfs, Werner; Brecher, Christian; Schmitt, Robert H.; Wagner, Wolfgang; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Induced pluripotent stem cells (iPS cells) represent a particularly versatile stem cell type for a large array of applications in biology and medicine. Taking full advantage of iPS cell technology requires high throughput and automated iPS cell culture and differentiation. We present an automated platform for efficient and robust iPS cell culture and differentiation into blood cells. We implemented cell cluster sorting for analysis and sorting of iPS cell clusters in order to establish clonal iPS cell lines with high reproducibility and efficacy. Patient-specific iPS cells were induced to differentiate into blood cells via embryoid body (EB) formation. EB size impacts on iPS cell differentiation and we applied cell cluster sorting to obtain EB of defined size for efficient blood cell differentiation. In summary, implementing cell cluster sorting into the workflow of iPS cell cloning, growth and differentiation represent a valuable add-on for standard and automated iPS cell handling.